ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN APBD KOTA SURABAYA TAHUN 2012-2015 - Karlina, Anis; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The result of the analysis shows that 1) the financial performance of the local government in thelocal revenue budget management of Surabaya cityin generalis stated to be less good in revenuevariant. It is proven that (a) the variant of the average of local revenue is under 100%, (b) localfinancial ratio isreviewedfrom the degree of decentralization shows the average is 53.54%, the averageof local financial independency is 176.05% ,the average of the growth of local revenue ratio is positive,2) The financial performance of local government inthe management of local budget of Surabaya cityin generally it can be said to be good. This is proven by (a) the average of the variant of localexpenditure is under 100%, (b) the average of the harmony of local expenditure when it is reviewedfrom the average of capital expenditure is 24.98% and the average of the operating expenditure is74.98%, (c) the average of the efficiency of local expenditure is under 100% which is 82.54%, (b) thegrowth of local expenditure has experienced the average growth is 11.00%, (c) the harmony of localexpenditure can be said that the municipal of Surabaya city has allocated most of theirexpenditurebudget for the average of operating expenditureis 90.33% when it is comparedto the average of capitalexpenditure is 9.57%,(d) the efficiency of local expenditure shows that the average is under 100%.Keywords: Local financial, revenue budget, expenditure budget, financial performance.